Stratigraphy and eruption history of maars in the Clear Lake Volcanic Field, California - Ball, Jessica L. (Frontiers in Earth Science, 2022)
The Clear Lake Volcanic Field (CLVF) is the northernmost and youngest field in a chain of volcanic provinces in the California Coast Range mountains. Effusive and explosive volcanic activity in the field has spanned at least 2.1 million years, with the youngest eruptions comprising a series of maar craters at the edges of, and within, Clear Lake itself. This work documents the first direct ages for many of these maar deposits, and builds the stratigraphic basis for interpreting eruptive processes and dynamics of the young eruptions which produced them. Detailed stratigraphy has distinguished maar eruption products from other monolithologic pyroclastic deposits (previously mapped as a single unit), and established a set of 6 eruption facies based on maar deposit lithology, grain size parameters, and depositional structures. Radiocarbon dates from carbon films found on clasts at 3 outcrops have constrained several of these maar eruptions to ~8500 – 13,500 years BP, coinciding with eruptive periods previously estimated based on lake core tephrachronology. Part of this period also coincides with indigenous occupation (< 12,000 years BP), which suggests that oral histories of Pomo and other local tribes may contain descriptions of volcanic phenomena experienced by local residents of the CLVF. Collaboration between volcanologists and indigenous historians may add a valuable human dimension to the youngest eruptions of the Clear Lake Volcanic Field; combined, geologic and ethnographic avenues of research will help build a richer eruption history for future volcanic hazard assessment.